2022
DOI: 10.1371/journal.pone.0269101
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in outcomes from mild traumatic brain injury eight years post-injury

Abstract: The long-term effects of mild TBI (mTBI) are not well understood, and there is an ongoing debate about whether there are sex differences in outcomes following mTBI. This study examined i) symptom burden and functional outcomes at 8-years post-injury in males and females following mTBI; ii) sex differences in outcomes at 8-years post-injury for those aged <45 years and ≥45 years and; iii) sex differences in outcomes for single and repetitive TBI. Adults (≥16 years at injury) identified as part of a populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 59 publications
0
15
1
Order By: Relevance
“…This pattern may reflect differences in demarcating change across measures (reliable change scores were only available for BTACT and BSI) or that factors independent of cognitive and psychiatric decline can also adversely affect functional independence. In contrast with previous findings, 8,[28][29][30][31] this study did not observed greater rates of decline among those with a history of comorbid health conditions, and future studies are needed to identify factors not currently considered that may influence worse longer-term outcomes after TBI.…”
Section: Discussioncontrasting
confidence: 99%
“…This pattern may reflect differences in demarcating change across measures (reliable change scores were only available for BTACT and BSI) or that factors independent of cognitive and psychiatric decline can also adversely affect functional independence. In contrast with previous findings, 8,[28][29][30][31] this study did not observed greater rates of decline among those with a history of comorbid health conditions, and future studies are needed to identify factors not currently considered that may influence worse longer-term outcomes after TBI.…”
Section: Discussioncontrasting
confidence: 99%
“…Although males represent at least 60% of all TBI cases, females with the same TBI severity experience worse symptoms than males. [69][70][71]…”
Section: Discussionmentioning
confidence: 99%
“…LinearSVCs were applied to differentiate mTBI patients from controls and mTBI patients with complete or incomplete recovery using the dMRI maps, sex and age. Sex and age were included as they have previously been shown to affect both the quantitative metrics obtained with DTI (FA and MD), as well as outcome after mild TBI [51][52][53][54] . The linearSVCs were either trained on the voxel-or ROI-wise FA and MD images 1) non-harmonized, 2)…”
Section: Machine Learningmentioning
confidence: 99%